Review of three-phase inverters control for unbalanced load compensation - Raef Aboelsaud; A. Ibrahim; Alexander G. Garganeev (Institute of Advanced Engineering and Science, 2019)
In the microgrid systems, three-phase inverter becomes the main power electronic interface for renewable distributed energy resources (DERs), especially for the islanded microgrids in which the power quality is easily affected by unbalanced and nonlinear loads, this is due to the fact that the voltage and frequency of the microgrid are not supported by the main power grid but determined only by the inverters. Therefore, the compensation of the load unbalances and harmonics in autonomous microgrid inverters are getting more attention in power quality research areas. The main purpose of this paper is to represent an overview of the control strategies of various inverters for unbalanced load compensation